The impact of Brain-Based Learning on critical and creative thinking in English Language Teaching - Winantaka, Binar (Jurnal Ilmiah WUNY, 2024)
This paper investigates the impact of Brain-Based Learning (BBL) strategies on fostering critical and creative thinking skills in English language teaching. In the context of 21st-century education, where the demands for innovation, critical thinking, and problem-solving are paramount, BBL emerges as a pedagogical approach that aligns teaching methods with cognitive science principles. Through a qualitative exploration of teacher perspectives and a quantitative analysis of classroom outcomes, this study highlights how BBL encourages the development of both hemispheres of the brain, promoting not only logical reasoning but also imaginative problem-solving. The findings underscore the potential of BBL to transform traditional English language teaching (ELT) practices by fostering a more holistic, engaging, and dynamic learning environment. Practical recommendations for integrating BBL into English classrooms are also provided..